STUDI KELAYAKAN PENGEMBANGAN INVESTASI UNIVERSITAS DILI (UNDIL) DI TIMOR-LESTE - Elisa, Ida; I Gusti Bagus, Wiksuana; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
The development of world education is increasing rapidly from day to day along with the progress of science and technology makes it possible for UNDIL to be part in making learning process fully supported and increases the quality of its graduates so that they can best serve the nation and state of Timor-Leste. The objective of this research was to indenti
Keywords: Feasibility study, Investment Development UNDIL